An efficient chiral sensing platform based on graphene quantum dot–tartaric acid hybrids. Issue 87 (5th September 2016) - Yu, Yin; Liu, Wenjie; Ma, Jianfeng; Tao, Yongxin; Qin, Yong; Kong, Yong
Abstract : Hybrids of GQDs-l -(+)–TA and GQDs-d -(−)–TA are used for the construction of a pH-sensitive chiral sensing platform. Abstract : Graphene quantum dots (GQDs) and tartaric acid (TA) were successively electrodeposited onto the surface of a glassy carbon electrode (GCE). Due to the intrinsic chirality of l -(+)-TA and d -(−)-TA and the signal amplification function of GQDs, the GQDs–TA hybrid modified GCE could be regarded as an efficient electrochemical chiral sensing platform and used for chiral recognition of tryptophan (Trp) isomers. The recognition efficiency with the proposed GQDs–TA is significantly higher than that with TA alone. Of particular interest, GQDs-l -(+)–TA and GQDs-d -(−)–TA exhibit completely opposite selectivity toward l -Trp and d -Trp. Also in this work, the pH-sensitive enantiorecognition of the GQDs–TA hybrids was investigated.